Comparison of three non-insulin-based insulin resistance indexes in predicting the presence and severity of coronary artery disease - Wu, Zhenguo; Cui, Huiliang; Li, Wei; Zhang, Yerui; Liu, Li; Liu, Zaibao; Zhang, Wencheng; Zheng, Tengfei; Yang, Jianmin (Frontiers in Cardiovascular Medicine, 2022)
Background: Insulin resistance (IR) has emerged as a risk factor for coronary heart disease (CAD), but there is currently insufficient data on the association of non-insulin-based IR indexes [triglyceride (TG)/high‐density lipoprotein cholesterol (HDL-C) ratio; triglyceride and glucose (TyG) index; and metabolic score for IR (METS-IR)] with the presence and severity of CAD. Thus, the present study aimed to examine the relationship between these three non-insulin-based IR indexes and CAD as well as to further compare the predictive values of each index. Methods: In total, 802 consecutive patients who underwent coronary angiography for suspected CAD from January 2016 to April 2017 were included in this study and were divided into the control group (n = 149) and CAD group (n = 653) according to the angiography results. The TG/HDL-C ratio, TyG index, and METS‐IR were calculated according to the corresponding formulas. The severity of CAD was evaluated using the Gensini score (GS). The relationship of the TG/HDL-C ratio, TyG index and METS-IR with CAD was analyzed, and the predictive values of the indexes were compared. Results: The TG/HDL-C ratio, TyG index, and METS-IR in the CAD group were significantly higher than those in control group. The TG/HDL-C ratio and METS-IR in the high GS group were significantly higher than those in the non-high GS group. Multivariate logistic regression analysis showed that the TG/HDL-C ratio and METS-IR were independent predictors for the presence of CAD [adjusted odds ratio (OR) (95% confidence interval (CI)): 1.32 (1.02-1.70) and 1.65 (1.32-2.05), respectively], whereas only the METS-IR was an independent predictor of the severity of CAD [adjusted OR (95% CI): 1.22 (1.02-1.47)]. Further subgroup analysis indicated that statistical significance was observed only among males, younger patients (≤ 60), and patients with prediabetes mellitus (PDM). Receiver operator characteristic (ROC) analysis showed that the METS-IR had the highest predictive value for the prediction of both the presence and severity of CAD. Conclusion: The TG/HDL-C ratio, TyG index, and METS-IR are valuable predictors of the presence and severity of CAD, and the METS-IR has the highest predictive value among the three non-insulin-based IR indexes.